The children of Abraham : Judaism, Christianity, Islam - Peters, F. E. (Francis E.) (Princeton, N.J. : Princeton University Press, 2006)
"F. E. Peters, a scholar without peer in the comparative study of Judaism, Christianity, and Islam, revisits his pioneering work after twenty-five years. Peters has rethought and thoroughly rewritten his classic The Children of Abraham for a new generation of readers-at a time when the understanding of these three religious traditions has taken on a new and critical urgency." "Peters traces the three faiths from the sixth century B.C. when the Jews returned to Palestine from exile in Babylonia, to the time in the Middle Ages when they approached their present form. The book's text is direct and accessible with thorough and nuanced discussions of each of the three religions. Updated footnotes provide the reader with expert guidance into the highly complex issues that lie between every line of this stunning and timely new edition of The Children of Abraham. Book jacket."--BOOK JACKET.
Introduction : the Scriptures : some preliminary notions -- The promise and the heirs -- A contested inheritance -- Community and hierarchy -- The law -- Scripture and tradition -- The worship of God -- Renunciation and aspiration -- Thinking and talking about God -- Epilogue : sacred history.
Includes bibliographical references and index.
Keywords: Judaism -- History -- To 1500.; Christianity; Islam -- History -- To 1500.